مدى توافر متطلبات تطبيق الإدارة الإلكترونية بصندوق الضمان الاجتماعي بمدينة درنة الليبية - جبريل، وائل محمد Jebril, Wael Mohammed (مركز البحث وتطوير الموارد البشرية رماح ومختبر التنمية التنظيمية وإدارة الموارد البشرية جامعة البليدة 2 لونيسي علي الجزائر, 2017)
هدفت الدراسة إلى التعرف على مدى مستوى توافر متطلبات تطبيق الإدارة الإلكترونية بصندوق الضمان الاجتماعي بمدينة درنة من خلال المتطلبات الآتية: (البشرية، المالية، الإدارية، التقنية، الأمنية)، وقد تمثل مجتمع الدراسة في جميع مديري الإدارات الوسطى بصندوق الضمان الاجتماعي بمدينة درنة، والذي بلغ قوامه (68) مديرا، ونظرا لصغر حجم مجتمع الدراسة عليه قام الباحث بدراسته بالكامل، لضمان نتائج أقرب للواقع وأكثر قابلية للتعميم، ولتحقيق أهداف الدراسة اتبعت الدراسة منهج دراسة الحالة، فقد قام الباحث بتطوير استبانة، وتم التأكد من مصداقيتها ومعامل الثبات لها، وبعد توزيع الاستبانة تم استرجاع (41) استمارة صالحة للتحليل الإحصائي، ولتحليل بيانات الدراسة تم الاستعانة بالحاسب الآلي واستخدام برنامج إحصائي من خدمة البرمجيات الواردة في (SPSS)، حيث تم التوصل إلى العديد من النتائج يمكن إيجازها فيما يلي: كشفت الدراسة توافر متطلبات تطبيق الإدارة الإلكترونية مجتمعة بصندوق الضمان الاجتماعي محل الدراسة عند مستوى دلالة إحصائية 1% وبمستوى متوسط، كما بينت نتائج الدراسة توافر المتطلبات المالية والإدارية، في حين أظهرت الدراسة عدم توافر المتطلبات الأمنية، البشرية والتقنية، وأخيرا قدمت الدراسة مجموعة من التوصيات التي يؤمل اتباعها لتطبيق الإدارة الإلكترونية بصندوق الضمان الاجتماعي محل الدراسة.
The study aimed to identify the extent of the availability of the implementation of Electronic Management requirements at the social security fund in Derna through the following requirements: (human, financial, administrative, technical, and security). The community of the study is represented in all the the central department managers at the social security fund in the city of Derna. The number reached are (68) director. And due to the small size of the study population, the researcher decided to study it fully, to ensure that the results are closer to reality and more likely to circulate. To achieve the study objectives, the case study method was followed, and the researcher created a questionnaire, after confirming its validity and its reliability. After the distribution of the questionnaire, (41) valid form have been retrieved for statistical analysis. The analysis of the study data was done by computer and the use of statistical software from the software contained service (SPSS), and reached many results that can be summarized as follows: The study revealed the availability of the implementation of E- Management requirements combined at the social security fund understudy at the level of significance (1%) and came in a moderate. The results of the study showed the availability of financial and administrative requirements, while the study showed the lack of security requirements, human and technical. Finally, the study made a series of recommendations that will hopefully be followed to the implementation of E-Management at the social security fund under study.
Keywords: تكنولوجيا المعلومات -- الإدارة الرقمية -- الموارد البشرية -- البنية المعلوماتية -- المؤسسات الليبية